ПСИХОЛОГИЧЕСКИЕ ОСОБЕННОСТИ УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ - Сапарбаева, М. (SCIENCE and SOCIETY, 2018)
The article is devoted to the psychological culture in the context of that which the child is the aim, meaning and basic values regardless of his age, level of development to and social status. The article reveals at the primary school age of children more attentionis paid to the behavior than on personality‘s qualities and psychological conception of activity, the object of communication is also determined, the requirements, motives of communication, communicative tasks, solved by people during communication.